LABORATORIUM KIMIA VIRTUAL: ALTERNATIF PEMBELAJARAN KIMIA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA TADRIS KIMIA IAIN WALISONGO SEMARANG (Jurnal Inovasi Pendidikan Kimia, 2013)
The objectives of this study were to describe the efectiveness of using virtual chemistry laboratory to improve the chemistry students’ learning. The subjects of this study were the students at grade I of Tadris Kimia IAIN Walisongo Semarang in the academic year of 2011/2012.The subjects was 40 students. The research uses cluster random sampling technique. Class TK-IA is chosen as experimental class (the students who are taught using virtual chemistry laboratory), and class TK-IB is chosen as control class (the students who are not taught using virtual chemistry laboratory). The result showed that the average score for eksperimental class is 31,4 for the pre test and 74,4 for the post test. While the average for control class is 31,6 for the  pre test and 62,2 for the post test. The calculation using the t-test showed the value of the t-test is higher than the value of the t-table.the value of t-test is 4,332 while the value oft-table on alpha 5% is 2,02 (4,3322,02). It can be concluded that there is a significant difference in student’s learning between students who are taught using virtual chemistry laboratory than students who are not taught without it. So, we can conclude that using virtual chemistry laboratory is effective to improve the chemistry students’ learning.